-7x+-3x+2=8x+-8

Simple and best practice solution for -7x+-3x+2=8x+-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -7x+-3x+2=8x+-8 equation:


Simplifying
-7x + -3x + 2 = 8x + -8

Reorder the terms:
2 + -7x + -3x = 8x + -8

Combine like terms: -7x + -3x = -10x
2 + -10x = 8x + -8

Reorder the terms:
2 + -10x = -8 + 8x

Solving
2 + -10x = -8 + 8x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-8x' to each side of the equation.
2 + -10x + -8x = -8 + 8x + -8x

Combine like terms: -10x + -8x = -18x
2 + -18x = -8 + 8x + -8x

Combine like terms: 8x + -8x = 0
2 + -18x = -8 + 0
2 + -18x = -8

Add '-2' to each side of the equation.
2 + -2 + -18x = -8 + -2

Combine like terms: 2 + -2 = 0
0 + -18x = -8 + -2
-18x = -8 + -2

Combine like terms: -8 + -2 = -10
-18x = -10

Divide each side by '-18'.
x = 0.5555555556

Simplifying
x = 0.5555555556

See similar equations:

| 15x+4=17x-4 | | 8-5n+3n=48-80 | | 5(2x-5)=2(x+6)+13 | | 17-25+6=179 | | -1+2*2=y | | 2(t-2)+5=9 | | 87645754444444444444444444444444444444444444444444444444444444444444444444444444+1=87645754444444444444444444444444444444444444444444444444444444444444444444444445 | | -1+2*0=y | | -4(5p+3)-48=3(2p+6) | | 5x+7=-2-4x | | m/9=25/m | | 4+3i/5+5i | | -1+2*-2=Y | | 4x=204 | | -6/7(4t+6)=3/28t-11 | | 3/8=21/(t+4) | | 7-45z=5z+13 | | -2y+2=20 | | -21y+14=24y+-16 | | 4(12-u)/5=-4u+12 | | 24x+3=24 | | -8(3a-9)=0 | | y=-1/2*-2+2 | | (13x+45)+(19x+3)=180 | | -29+10y+7=3(4y-2)-4 | | 180-.14x=.29x | | 2(9x+7)-6x=3(4x+2)-9 | | 4x+7+2x=5 | | 2(1+x)/3=x+1 | | y=-1/2*-4+2 | | 180-.14=.29 | | 3x+7+x+8=39 |

Equations solver categories